Studi Literatur: Efektivitas Model Kooperatif Tipe Course Review Horay Dalam Pembelajaran IPA Di Sekolah Dasar - Munib, Achmad; Wulandari, Fitria (Universitas Nusantara PGRI Kediri, 2021)
Abstract: This study aims to determine the effectiveness of the Course Review Horay model in learning science in elementary schools. The method in this research uses qualitative research with data collection techniques, namely literature studies. Data collection used is by collecting, checking information or data about the findings that are different from books, proposals, various articles and journals that apply. Data that has been obtained, researched, and centered inside and outside efficiently and basically then described in a narrative. From the results of the research analysis showed that the value of the activeness and activities of students in science learning showed that there were differences in the understanding of students between cycle I and cycle II. That is, from several studies that have been applied using the Course Review Horay model, it shows that the learning effectiveness that students already have shows that they are less active in cycle I and in cycle II indicate an active category. Based on the literature study, it can be concluded that the CRH model can make it easier for students to learn, is able to make students interested or happy to learn science learning materials and this CRH model is very effective in being applied in elementary